Analysis of Chromosome 8 Copy Number Changes in Colorectal Cancers by Fluorescence In Situ Hybridization (FISH). - Yüce, Hüseyin; Etem, Ebru; Deveci, Şükriye Derya; Doğru, Osman; Özercan, İbrahim Hanifi; Elyas, Halit (Fırat University, 2007)
Objective: Colorectal cancer (CRC) is one of the most common malignancies worldwide. Colorectal carcinogenesis has associated with the progressive acquisition of a variety of genomic alterations by neoplastic cells, some of these have been linked to early stages of CRC development. The aims of this study (1) to identify alterations of chromosome 8 in primary colorectal carcinomas from Turkish patients and (2) to determine which alterations of chromosome 8 are early events during the development of colorectal carcinoma using fluorescence in situ hybridization (FISH). Materials and Methods: To reveal the significance of genetic abnormalities of the chromosome 8, 28 colorectal tumors were analyzed using FISH. The centromeric-probe for chromosome 8 was used for FISH. In each case, at least 200 nuclei were scored for each hybridization. Results: Monosomy in 3.6%, disomy in 39.3%, trisomy in 53.6% and tetrasomy in 3.6% of the analyzed adenomas were determined. Chromosome 8 gain was found in 5 of 8 (62.5%) nonpolypoid and 3of 9 (33.3%) polypoid cancers. There was statistically significant correlation between chromosome 8 gain and stage of CRC. Conclusions: There are several reports of chromosome 8 gain in solid tumors. FISH is a useful method to detect genetic abnormalities in solid tumors. It was shown that chromosome 8 gain FISH associated with the stage of CRC. Chromosome 8 monosomy may be a early event in CRC. Further studies involving more patients need to determine the importance of this alteration in CRC. ©2007, Firat University, Medical Faculty

Amaç: Kolorektal kanser (KRK) dünyadaki en yaygın malignansilerden biridir. Kolorektal karsinogenezis neoplastik hücrelerde meydana gelen çeşitli genetik değişikliklerin birikimiyle beraberlik göstermektedir. Bunlardan bazıları KRK gelişiminin erken safhalarında gerçekleşmektedir. Bu çalışmanın amacı, Floresans in situ Hibridizasyon (FISH) kullanılarak Türk primer kolorektal kanserli hastalarda kromozom 8 değişimlerini tanımlamak ve kromozom 8 değişimlerinin kolorektal kanserin gelişiminde erken bir olay olup olmadığını tespit etmektir. Gereç ve Yöntem: Kromozom 8'in genetik anomalilerinin anlamını göstermek için 28 kolorektal kanser FISH'le analiz edildi. FISH için kromozom 8 sentromerik prob kullanıldı. Her bir hasta için en azından 200 hücredeki sinyaller incelendi. Bulgular: Analiz edilen tümörlerin %3.6'sında monozomi, %39.3'ünde dizomi, %53.6'sında trizomi ve %3.6'sında tetrazomi saptandı. Kromozom 8 kazancı 8 nonpolipoid kanserin 5'inde (%62.5) ve 9 nonpolipoid kanserin 3'ünde (%33.3)'de bulundu. Kromozom 8 kazancı ve KRK evresi arasında istatistiki olarak anlamlı korelasyon vardı. Sonuç: Solit tümörlerde kromozom 8 kazancıyla ilgili birkaç çalışma vardır. FISH solit tümörlerdeki genetik anomalilerin tespiti için faydalı bir yöntemdir. Kromozom 8 kazancı ve KRK evresi arasında ilişki olduğu gösterildi. Kromozom 8 monozomisi KRK'da erken bir olay olabilir. Bu değişimin öneminin ortaya konması için KRK'da daha fazla hasta sayısı içeren çalışmaların yapılması gerekmektedir. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Kolorektal Kanserlerde Floresans in situ Hibridizasyon (FISH) Kullanılarak Kromozom 8 Kopya Sayı Değişimlerinin Analizi